Assessment on the knowledge and reported practices of women on maternal and child health in rural Sierra Leone: a cross-sectional survey. - Joseph Sam Kanu; Yuan Tang; Yawen Liu (PLoS ONE, 2014)
Globally, Sierra Leone is ranked among the countries with the worst maternal and child health indicators. The mortality of women and children is significantly higher compared with other developing countries. The death of women and children can be prevented by simple cost-effective community-based interventions. The aim of this present study was to learn the knowledge levels of women on maternal and child health, and treatment-seeking and preventive behaviours in rural Sierra Leone and provide appropriate suggestions for policy makers. Moreover, the study also aimed to evaluate the effect of a husband's involvement on health knowledge and practices of women in rural Sierra Leone.Women with at least a child of five years or below were interviewed in their households through a structured questionnaire. Characteristics of the households and of the respondents were collected and the number of correct answers given to the health knowledge and practice questions and their percentage distributions were tabulated and an overall health knowledge score was calculated.The mean score of the derived overall health-related knowledge was 61.6% (maximum of 91% and a minimum of 18%) with a standard deviation of 14.7% and a median of 63.3%. Multivariable regression analyses showed education and number of pregnancies are associated with knowledge score, with significantly improved health knowledge scores amongst those who accessed higher education. There were some inappropriate practices in hygiene and sanitation. However, vaccination coverage was high with almost 100% coverage for BCG.Based on the findings of this study, women's knowledge on maternal and child health care are inadequate in rural Sierra Leone. Health promotion activities focusing on prevention of diarrhoea, malaria and pneumonia, improvement in health-related knowledge on pregnancy, delivery, neonatal care and environmental sanitation would be invaluable.